ASSESSING THE IMPACT OF NURSE STAFFING RATIOS ON CLINICAL OUTCOMES IN MEDICAL AND SURGICAL ICU PATIENTS: A RETROSPECTIVE COHORT STUDY - Aziza Radhi Munawar Al-Rashidi, Abdullah Khalaf Mutarid Al-Anzi, Mohammad Awaid Saud Alanzi, Nouf Sadi Alshammry, Abdullah Mohammad Salum Al Hroth, Huda Sultan Saad Alyami (Chelonian Research Foundation, 2022)
Adequate nurse staffing is crucial in intensive care units (ICUs) to ensure safe quality care, but optimal nurse-patient ratios remain undefined. This retrospective cohort study aimed to examine associations between nurse staffing ratios and patient clinical outcomes among 750 patients admitted to medical and surgical ICUs in a tertiary hospital in Riyadh, Saudi Arabia. Nurse staffing was determined for each ICU unit-day as patient-nurse ratios. Outcomes assessed through chart review included in-hospital mortality, ICU length of stay, 30-day readmissions, and adverse events. Risk-adjusted regression modeling assessed the impact of staffing ratios on outcomes. A significant dose-response relationship was found, with higher patient-nurse ratios associated with increased mortality risk (odds ratio 1.15, 95% confidence interval 1.04-1.29). Ratios above 1:2 were also associated with longer ICU stays, higher 30-day readmission rates, and increased adverse events. Maintaining ratios at 1:2 or lower was associated with improved outcomes. Findings support recommendations to limit medical-surgical ICU nurse-patient ratios to a maximum of 1:2 to optimize patient outcomes.